Penerapan Media Animasi dalam Power Point pada Pembelajaran IPA terhadap Pengetahuan Siswa Berdasarkan Gender - Irmansyah, Irmansyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This research aims to determine the cognitive learning outcomes of class VIII students at SMP Negeri 5 Mataram through the application of animation media in power point. The research was carried out in the odd semester of the 2021/2022 academic year at SMP Negeri 5 Mataram. The subjects of this research were class VIII students at SMP Negeri 5 Mataram for the 2021/2022 academic year. The research method used was pre-experimental. The design used in this pre-experimental research was one group pretest-posttest. The instrument used to assess students' level of success is using essay learning outcomes tests. Data collection techniques use pretest and posttest. The data analysis technique uses a formula, namely the number of correct answer scores divided by the total score multiplied by one hundred. To calculate the N-Gain value, use the formula, namely the posttest score minus the pretest score divided by the maximum score minus the pretest score. The results of the research show that student learning outcomes based on gender show that male students obtained an average pretest score of 47.16 and a posttest of 53, while the average pretest score for female students was 53 and the average posttest score was 64.77. The N-Gain value for male students is 0.05 and the N-Gain value for female students is 0.25, and both are in the low category. Thus, it can be concluded that after using power point media and 3D animation, students' cognitive learning outcomes show an increase in learning outcomes compared to before.